8B.07: RESULTS FROM THE UK RENAL DENERVATION AFFILIATION- 246 CASES FROM 17 CENTRES. (June 2015) - Sharp, A.; Hameed, A.; Nightingale, A.; Martin, U.; Mark, P.; Mckane, W.; Cunnington, M.; Lobo, M.; Mahadevan, K.; Richardson, T.; Gerber, R.; Clifford, P.; et al.
Abstract : Objective: To describe the UK experience with Renal Denervation (RDN). Design and method: RDN may lower blood pressure (BP) in people with resistant hypertension. The UK Renal Denervation Affiliation is an independent, investigator-led initiative. Each centre had done >5 cases. A standardised dataset was collected retrospectively, anonymised and submitted to the coordinating centre for analysis. Results: Results from 246 cases from 16 centres are reported. Average cases per centre was 15. Five different ablation technologies were used: unipolar catheters in 198 and multipolar in 48. Mean age was 56.7 years, 53% female, 87% Caucasian and 27% diabetes. Previous stroke/TIA - 24%; myocardial infarction - 15%; proteinuria - 26%. Patients were screened by a mean of 1.6 specialists with an interest in hypertension. 86% attended specialist hypertension clinics. On average 4.7 drugs were used before RDN; 95% were on 3+ drugs; 90% were on RAS blockers, 90% diuretics and 56% aldosterone antagonists at time of RDN. Pre-RDN mean office BP was 186/102 mmHg. Ambulatory blood pressure monitoring (ABP) data were available for 179 patients (73%). Average pre-RDN ABP was: daytime - 170/98; night - 154/86. Average follow-up was 10.7 months. Mean Office BP post-RDN was 164/93, a fall of 22/9 mmHg (P < 0.001). In 24%, office SBP fell 40+ mmHg. On average, 0.8 drugs were withdrawn per patient and 0.3 drugs added between RDN and follow-up. Mean daytime ABP after RDN was 158/92 and nighttime ABP 145/81 - fall in daytime ABP was 12/6 (p < 0.001). 18% had a drop in day systolic ABP of >20 mmHg. A decrease in GFR >25% was seen at 10 months in 5% patients. Otherwise, no significant complications were seen. Conclusions: In a cohort of 246 patients from 16 UK centres who had undergone renal denervation, a significant fall in blood pressure was observed. Office BP fell by 22/9 mmHg. Daytime ambulatory BP fell by 12/6 mmHg. Carefully selected patients with resistant hypertension exhibited significant BP reduction following RDN. This was a group with severe hypertension who had been well characterised in specialist hypertension clinics. Drug additions/withdrawals did not appear to explain the BP fall.